Dukungan Psikologi/ Sosial Menurunkan Tingkat Kecemasan Penderita Pasca Covid-19 Di Kota Semarang - Fiktina Vifri Ismiriyam; Mukhamad Musta’in (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
The corona virus or known as Covid-19 has become a pandemic disease because this virus has spread to various countries and is almost infecting all over the world, including Indonesia. WHO defines a pandemic as a condition of the world's population and the potential to cause falls and illness. The Covid-19 pandemic has had an impact on various sectors of life such as the economy, education and social life. Covid-19 cases in the city of Semarang as of August 17, 2021, there were 84,978 confirmed cases, 197 confirmed cases, 65,396 recovered cases and 4,307 deaths. Sambiroto Village is included in the yellow zone. In the Sambiroto sub-district, not a few have also experienced Covid-19, although without showing symptoms of the disease, it has an impact on the psychology of the residents. Various psychological reactions shown by residents with the presence of Covid-19, ranging from mild anxiety to stress/panic. The purpose of this community service is to provide psychological/ social encouragement to post-Covid-19 sufferers so that they lead to adaptive behavior. The results of the service showed that most of the participants were women, the most type of work was housewives, the most education was high school and psychological/ social support was able to reduce the level of anxiety in residents in the Sambiroto village, Semarang City.